Identify training needs: a case study of Syarikat Sesco Berhad / Silvia Joseph - Joseph, Silvia (2007)
The primary objective of this study is to study on how employee perceived the training provided by the organization. How effective training can improve employee job performance? To study other factors that can be consider by the organization to motivate and encourage job performance among employees. The main research objective is to identify and study training need of different type of department, working experience, education background and nature ofjob, and also to study the management training that can be organized by the Company. The employee of Syarikat Sesco Berhad. Head Quarters and Kuching Regional Office were selected as the respondents for this research. Out of 150 respondents, only 72 sets of questionnaires were successfully collected and only 67 sets of questionnaires were valid to be analyzed. Survey was also carried out in the month of August and September 2007.